Malaysian bilateral exports and bilateral real exchange rates - Yusoff, Mohammed (Faculty of Economics, Universiti Utara Malaysia, 2007)
This paper analyzes the performance of Malaysian bilateral exports to its major importing countries: the United States, Japan, and Singapore and then investigates whether the export performance could be improved through depreciation or devaluation of domestic currency using cointegration technique and VECM. The cointegration test suggests that real exports, real exchange rates, real imports, and foreign income are cointegrated. The estimated long-run export equations indicate that the real exchange rates, real foreign income, and real imports are important determinants of exports. The major policy implication from this study is that a devaluation or depreciation of ringgit could improve the competitiveness of Malaysian exports. Keywords: exports, real exchange rates, Malaysia